2022
DOI: 10.1007/s10035-021-01197-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the wall effects of packed concentric cylinders and angular walls on granular bed porosity

Abstract: The effect of added wall support on granular bed porosity is systematically studied to elucidate performance enhancements in filtration processes achieved by using inserts, as demonstrated experimentally (Bandelt Riess et al. in Chem Eng Technol 2018, 2021). Packed beds of spheres are simulated through discrete element method in cylinders with different internal wall configurations. Three containing systems are generated: concentric cylinders, angular walls, and a combination of both. Variations of particle si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…the number of particle layers along the channel height is too small to neglect the contribution of the flow near the channel surface. [56][57][58][59] Secondly, because of the heterogeneous microstructure 60,61 of the accumulation with the presence of void zones, 44,57,62 which inevitably favours an heterogeneous flow through the porous structure. We also observed that when we get closer to the CCC, at I = 100 mM, the value of f remains unchanged (Fig.…”
Section: Flow Conditions Inside the Particle Accumulationmentioning
confidence: 99%
“…the number of particle layers along the channel height is too small to neglect the contribution of the flow near the channel surface. [56][57][58][59] Secondly, because of the heterogeneous microstructure 60,61 of the accumulation with the presence of void zones, 44,57,62 which inevitably favours an heterogeneous flow through the porous structure. We also observed that when we get closer to the CCC, at I = 100 mM, the value of f remains unchanged (Fig.…”
Section: Flow Conditions Inside the Particle Accumulationmentioning
confidence: 99%